Practical Utility of the Revised European‐American Classification of Lymphoid Neoplasms for Japanese Non‐Hodgkin's Lymphomas - Izumo, Toshiyuki (Jpn J Cancer Res, 2000)
A clinicopathological study of 515 non‐Hodgkin's lymphoma (NHL) cases was performed using the revised European‐American classification of lymphoid neoplasms (REAL classification) in an HTLV1‐nonendemic area of Japan. The following characteristics were revealed: 1) frequency of extranodal lymphomas was high (59%) with 79% B‐cell lymphomas in this series, while the overall ratio of B:T/NK lineage was 3.7:1; 2) the most common type was the diffuse large B‐cell lymphoma (46%), follicle center lymphomas occurred at an incidence lower (15%) than that in European and American populations, and marginal zone B‐cell lymphomas accounted for as much as 12%; 3) peripheral T‐cell lymphomas were common (19%), with the unspecified type predominant (11%), while adult T‐cell lymphomas were present at a level equivalent to that among European and American patients (1%). Clear segregation of survival curves was rated according to cell lineage and B‐cell lymphomas had a better prognosis than T/NK‐cell lymphomas. Furthermore, new subtypes in the REAL classification, such as marginal zone B‐cell and mantle cell lymphomas, exhibited distinct curves. Taken altogether, the REAL classification demonstrated advantages for assessment of Japanese NHL cases.